Exploring academic dishonesty among undergraduate criminal justice majors: A research note - Coston, Charisse T. M. (American journal of criminal justice, 1998)
The nature and extent of academic dishonesty among undergraduate criminal justice majors at a mediumsized university in the Southeastern US were explored. Using several theories of deviance as theoretical frameworks, the research sought to investigate the motivations for such behaviors. Criminal justice majors indicated that they are aware of, have engaged in, and plan to become involved in various low, medium, and high levels of academically dishonest behavior in the future. Additionally, study results reveal that specific acts defined as academically dishonest by the university and individual professors are not viewed as dishonest by students. Implications and directions are discussed in light of these research results.